Related formulas

Integral of $\frac{x^2}{\sqrt{x^2+6}}$ with respect to x

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Basic Integrals

· Constant factor Rule

The integral of a constant by a function is equal to the constant multiplied by the integral of the function

$\int cxdx=c\int xdx$
· Sum Rule of Integration

The integral of the sum of two or more functions is equal to the sum of their integrals

$\int\left(a+b\right)dx=\int adx+\int bdx$

Trigonometric integrals

$\int\sec\left(x\right)\tan\left(x\right)^2dx=\int\sec\left(x\right)^3dx-\int\sec\left(x\right)dx$

The integral of the secant function is given by the following formula, $\displaystyle\int\sec(x)dx=\ln\left|\sec(x)+\tan(x)\right|$

$\int\sec\left(x\right)dx=\ln\left|\sec\left(x\right)+\tan\left(x\right)\right|+C$

Simplify the integral $[root]$ applying the reduction formula, $\displaystyle\int\sec(x)^{n}dx=\frac{\sin(x)\sec(x)^{n-1}}{n-1}+\frac{n-2}{n-1}\int\sec(x)^{n-2}dx$

$\int\sec\left(x\right)^ndx=\frac{\sin\left(x\right)\sec\left(x\right)^{\left(n-1\right)}}{n-1}+\frac{n-2}{n-1}\int\sec\left(x\right)^{\left(n-2\right)}dx$

Basic Derivatives

· Derivative of the linear function

The derivative of the linear function is equal to $1$

$\frac{d}{dx}\left(x\right)=1$

Derivatives of trigonometric functions

Taking the derivative of secant

$\frac{d}{dx}\left(\sec\left(x\right)\right)=\sec\left(x\right)\tan\left(x\right)\frac{d}{dx}\left(x\right)$